Visitor Circulation Patterns in Mountain Tourism Areas: A Comparative Study of Ketep Pass, Puncak Suroloyo, and Nepal Van Java - Hadiyanto, Priyo; Nuzuluddin, Taufiq Rizza; Andadari, Tri Susetyo (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2026)
Mountain tourism destinations represent environmentally sensitive landscapes characterized by steep terrain, limited accessibility, and dynamic visitor movement patterns. In many Indonesian highland tourism areas, circulation systems evolve without comprehensive spatial integration, resulting in congestion, pedestrian–vehicle conflicts, safety risks, and diminished visitor experience. This study aims to identify, classify, and comparatively analyze visitor circulation patterns in three mountain tourism destinations in the Magelang region: Ketep Pass, Puncak Suroloyo, and Nepal Van Java. A qualitative descriptive-comparative approach was employed through a literature review, field observation, spatial mapping, and classification of circulation typologies. The analytical framework integrates architectural circulation theory and sustainable tourism principles. The findings reveal three distinct typologies: formal linear-structured circulation (Ketep Pass), topography-adaptive linear-natural circulation (Puncak Suroloyo), and community-integrated linear circulation (Nepal Van Java). The study demonstrates that circulation morphology is influenced by terrain gradient, infrastructure planning intensity, and socio-spatial integration. This research contributes a contextual circulation model for mountain tourism planning that emphasizes terrain responsiveness, pedestrian prioritization, and community participation to achieve sustainable spatial development.